Employee Perceptions on the Implementation of Talent Management at PT Pegadaian Office Region VIII Jakarta - Hani Rahma Ardhani; Fibria Indriati (International Journal Labs, 2023)
PT Pegadaian Regional Office VIII Jakarta is an organization that is committed to managing its internal talent well. However, to ensure the effectiveness of this program, it is important to evaluate employee perceptions of talent management implementation. This research aims to describe employee perceptions regarding the implementation of talent management in this regional office. This research uses a qualitative approach. Data collection techniques in this research were carried out using interviews and a literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation, and conclusion. The research results show that employees of PT Pegadaian Regional Office VIII Jakarta generally have a positive perception of the implementation of talent management. Employees assess that the implementation of talent management in this regional office has helped them to improve their skills and knowledge, helped employees to develop their careers, and helped employees to contribute better to the organization. However, several things need to be improved regarding the implementation of talent management, including communication about the implementation of talent management that needs to be improved, the talent selection and development process needs to be optimized so that the right employees can be identified and developed, and the evaluation and compensation system needs to be integrated with the implementation of talent management so that employee performance can be measured and rewarded more effectively.